2007
DOI: 10.1021/ef060386k
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Solubility Models to Predict Asphaltene Instability in Live Crude Oils

Abstract: This paper describes a thermodynamic solubility model to predict the asphaltene stability/instability of live crude oil systems under reservoir conditions. The model uses the Hildebrand solubility parameter of stock tank oil to predict the solubility parameter of the live oil under reservoir conditions by incorporating the dissolved gas composition along with the pressure−volume−temperature (PVT) properties of the live oil. Precipitation and deposition of asphaltenes from crude oils resulting from changes in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 14 publications
0
58
0
Order By: Relevance
“…They identified the intersection point of these two trends as the asphaltene precipitation onset. Kraiwattanawong et al (2007) stated that selecting the minimum point of light absorbance versus volume fraction of precipitant plot results in an inaccurate determination of the asphaltene precipitation onset. They showed that plotting the derivative of light absorbance with respect to volume fraction of precipitant versus volume fraction of precipitant provides a more precise value of asphaltene precipitation onset.…”
Section: Light Scattering Technique (Lst)mentioning
confidence: 99%
“…They identified the intersection point of these two trends as the asphaltene precipitation onset. Kraiwattanawong et al (2007) stated that selecting the minimum point of light absorbance versus volume fraction of precipitant plot results in an inaccurate determination of the asphaltene precipitation onset. They showed that plotting the derivative of light absorbance with respect to volume fraction of precipitant versus volume fraction of precipitant provides a more precise value of asphaltene precipitation onset.…”
Section: Light Scattering Technique (Lst)mentioning
confidence: 99%
“…nC 5 or nC 7 ) at standard lab conditions. The majority of the previous works on thermodynamics of asphaltene stability are based on the assumption that asphaltene destabilization is an instantaneous phenomenon and the kinetics effects associated with asphaltene precipitation and aggregation have not been considered . The many experiments reported to date indicate that asphaltene aggregation is a gradual and time‐dependent process that occurs very slowly …”
Section: Introductionmentioning
confidence: 99%
“…reduction of live oil solubility parameter from initial pressure to bubble point pressure) is also because fluid expanding results in decreasing interactions among molecules/particles [44]. After the bubble point is reached, dissolved gas starts escaping from the liquid phase causing the live oil solubility parameter to increase with a pressure reduction because gas has low solubility parameter [44,45]. As a result of above discussion, the solubility parameter of live oils is found to be a linear function of their densities measured at high pressures and temperatures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%